Perancangan Sistem Informasi Pemrosesan Order Produk Ortosa Prostesa Di Instalasi Ortotik Prostetik Rumah Sakit Ortopedi Prof.Dr. R. Soeharso Surakarta - Muh. Hisyam; Irwan Iftadi; Anwar Efendi (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2007)
Orthotic and Prosthetic Instalation of Ortopedic Hospital of production unit in the making of prosthesis orthosis in Indonesia. So far there is no technician status which contains finishing time for all orders which are being processed . This condition causes the delay in order finishing time. Therefore, it needs information system which can make task allocation model (new order) better. After system analysis was done to find out the needs of the system, the information system of the process of prosthesis orthosis product order is designed. The existing system analysis is carried out by using IDEF0 language while the setting up plan for the information system proposed is carried out by using object oriented approach and using UML language.At the database setting up level by using Relational Database Management System (RDBMS) approach needs adjustment from object oriented approach to relational approach, then user interface model are designed later. The next step, program codes were made by giving attention to use case diagram and interaction diagram . From the setting up for information system were found out some inputs in the forms of forms for login, the data of patients, products, raw materials needed, raw materials, order, and technician data. The output were in the forms of early warning for order, order reports, the order slips, the letter of order and the acknowledge receipt of the order. From the validation result to the functions in the application was found out that the functions tested were valid or worked well.